DFT-assisted XANES simulations to discriminate different monomeric CuII species in CHA catalysts. (October 2020) - Pankin, I.A.; Borfecchia, E.; Martini, A.; Lomachenko, K.A.; Lamberti, C.; Soldatov, A.V.
Abstract: Herein, we present Cu K-edge XANES (X-ray Absorption Near Edge Structure) simulations for different framework interacting Z-Cu II species proposed to form as an active site after high-temperature activation in Cu-exchanged chabazite zeolites, representing promising materials for selective catalytic reduction of NOx in the presence of ammonia and direct conversion of methane to methanol. We critically compare the simulated spectra to previously collected data for an O2 -activated Cu-chabazite sample. Density of states (DOS) calculations allow us to get more insights in describing the nature of XANES features observed in the simulated spectra. To demonstrate the potential of the method, we finally explore the impact of systematic variations of selected structural parameters on the theoretical XANES features. Highlights: XANES simulations can be applied to discriminate between different Cu II sites in CHA. XANES can effectively distinguish three- and four-fold coordinated Cu II species. Simulations for modified models reflect the consecutive evolution of XANES spectra. Partial DOS calculations allow to explore the origin of XANES features in Cu-CHA.